Beanstalk Company business plan on urban farming using SNAP hydrophonics technology - Tolentino, Francis (University of the Philippines Diliman, Technology Management Center, 2012)
The Beanstalk Company is an agri-business institution that will be engaged in urban farming. Managed by and registered under the Philippine law as a sole proprietor, Beanstalk Company will acquire and harness SNAP (Simple Nutrients Addition Program) hydroponics technology as its method of urban farming and as its core technology for developing and producing its crops. The company's main business is to distribute its crop produce directly to consumers and mainly to small and medium businesses within a 15 kilometer radius of its farm located in Cainta, Rizal. On its launch, the company will position itself as a product specialist supply chain with a flexible distribution structure which would mean it will focus producing lettuce and its common and marketable variety as the company's main product and produce.